Forestry Taxation in Africa : The Case of Liberia - Thomas, Saji (IMF Working Papers; Working Paper, 2005)
Countries generally tax the forestry sector to achieve the twin objectives of revenue maximization and sustainability of logging levels. In an ideal world of perfect markets and information, auctions would be the best instrument to determine the price of extraction rights. However, a number of factors-including a lack of information on the forest resources under consideration, uncertainties as to the stability of property rights over time, and a lack of access to credit-have limited the use of auctions so far, particularly in low-income countries. To establish transparency of the forestry sector's financial flows, this paper discusses a radical simplification of Liberia's current timber tax structure, including a proposal to reduce the sector's current tax system to two instruments, an area tax and an export tax.